Transmission System Augmentation Based on the Concepts of Quantity Withheld and Monopoly Rent for Reducing Market Power - Hesamzadeh, M.; Hosseinzadeh, N.; Wolfs, Peter (IEEE, 2010)
This paper proposes two mathematical structures for considering the market power effect of transmission capacity in transmission augmentation assessment. These mathematical structures use the concepts of monopoly rent and quantity withheld in economics for market power modeling in the assessment process of transmission augmentation. The simultaneous-move and sequential-move games in applied mathematics are used to model the interactions of the transmission network service provider, generating companies, and the market management company in the proposed mathematical structures. The solution concept of Nash equilibria is reformulated as an optimization problem, and the multiple Nash equilibria is tackled through an introduced concept termed worst Nash equilibrium. A numerical solution is developed to solve the proposed mathematical structures. The numerical solution is an island parallel genetic algorithm nested in a standard genetic algorithm. The six-bus Garver's example system and the IEEE 14-bus test system are modified and studied. The results prove the strong mechanism of the developed structures for modeling the market power effect of transmission capacity in the assessment of transmission augmentation.